Evaluation of the Effects of Dual Antiplatelet Therapy on Guided Bone Regeneration in Peri-Implant Bone Defect - Kobat, Mehmet Ali; Dundar, Serkan; Bozoglan, Alihan; Gelen, Mehmet Ali; Artas, Gokhan; Kirtay, Mustafa; Habek, Osman (Lippincott Williams & Wilkins, 2023)
In this study, the authors aim to investigate the effect of dual antiplatelet agents on peri-implant-guided bone regeneraation by studying a sample of rats with titanium implants in their tibias. The rats were randomly divided into 5 groups: acetylsalicylic acid (ASA) (n=10), treated with 20 mg/kg of ASA; ASA+CLPD (Clopidogrel): (n=10), treated with 20 mg/kg of ASA and 30 mg/kg of clopidogrel; ASA+PRSG (Prasugrel): (n=10), treated with 20 mg/kg of ASA and 15 mg/kg of prasugrel; ASA+TCGR (Ticagrelor): (n=10), treated with 20 mg/kg of ASA and 300 mg/kg of ticagrelor; and a control group (n=10) received no further treatment after implant surgery. Bone defects created half of the implant length circumferencial after implant insertion and defects filled with bone grafts. After 8 weeks experimental period, the rats sacrified and implants with surrounding bone tissues were collected to histologic analysis; bone filling ratios of defects (%) and blood samples collected to biochemical analysis (urea, creatinine, aspartate aminotransferase, alanine aminotransferase, phosphorus, magnesium, alkaline phosphatase, calcium, and parathormone). A statistically significant difference was not detected between the groups for all parameters (P>0.05). When the percentage of new bone formation was examined, it was found that there was no statistically significant difference between the groups (P>0.05). Antiplatelet therapy may not adversely affect guided bone regeneration in peri-implant bone defects.
Keywords: Antiplatelet drugs; dual antiplatelet therapy; guided bone regeneration; guided tissue regeneration; peri-implant bone defect